Analisa Pengaruh Intellectual Capital dan Inventory Turnover terhadap Profitabilitas Perusahaan (Studi Kasus pada Perusahaan Ritel dan Grosir yang terdaftar di BEI tahun 2009 – 2013) - Ardhan Jendra (Business Accounting Review, 2015)
This study aimed to analyze the influence of intellectual capital and inventory turnover on the profitability of the company. This study used several variables that were identified as factors affecting profitability include the following: Value Added Human capital (VAHU), Structural Capital Value Added (STVA), and Value Added Capital employed (VACA). The population used in this study was companies engaged in the retail and wholesale sectors. The method of data processing was performed by using multiple linear test. This study uses a quantitative approach. To test the hypothesis must meet the criteria, namely R2 test, t test and F test. The result revealed that the intellectual capital and inventory turnover simultaneously had significant affect on profitability. But partially, VAHU and ITO did not significantly affect profitability, while STVA and VACA significantly affect profitability.